MEDICATION ERRORS: IS IT MORE IMPORTANT TO FIND AND PUNISH THE GUILTY ONE, OR TO REDUCE THE LIKELIHOOD OF RECURRENCE OF AN ERROR? - Ausrine Amsiejute (European Scientific Journal, ESJ, 2015)
It is always emphasised in case-law that the nature of medical personnel’s liability is determined by significance of health care as a social activity area, and the related need to ensure adequate health care services to the public. People who work in the medical field make errors like everyone else. When it comes to medication errors, it is usually considered that these errors are the most preventable, but also they are the errors which may result in the greatest negative consequences. Unfortunately, the entrenched traditional approach to medication errors, which can be described as “naming, blaming, shaming and punishing”, does not increase safety in medicine. This enrooted perception associating error with nonprofessionalism, lack of attention and negligence, not only discourages learning from mistakes, but on the contrary – promotes their hiding.